Understanding unethical behaviors at the university level: a multiple regression analysis. Issue 4 (19th May 2021) - Julián, Martín; Bonavia, Tomas
ABSTRACT: Unethical behaviors such as corruption pose an important challenge for students, professors, and other university members. We aimed to clarify students' willingness to engage in corruption in a Spanish public university. In all, 3, 475 undergraduate, postgraduate, and PhD students completed an online questionnaire assessing four corruption scenarios: favoritism, bribery, fraud, and embezzlement. Multiple regression analysis suggested that justifiability, risk perception, and perceived corruption played a key role in explaining corrupt intention. Behavioral intention to engage in corruption is a complex phenomenon explained by not only peers' behaviors, but also individuals' justifications of their acts and risk perceptions.